2021
DOI: 10.3390/metabo11030159
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Metabolites in Colorectal Cancer: Basic and Clinical Implications

Abstract: Colorectal cancer (CRC) is one of the leading cancers that cause cancer-related deaths worldwide. The gut microbiota has been proved to show relevance with colorectal tumorigenesis through microbial metabolites. By decomposing various dietary residues in the intestinal tract, gut microbiota harvest energy and produce a variety of metabolites to affect the host physiology. However, some of these metabolites are oncogenic factors for CRC. With the advent of metabolomics technology, studies profiling microbiota-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 122 publications
(76 reference statements)
0
32
0
Order By: Relevance
“…There are substantial reports that the general gut microbiota is associated with the initiation and progression of CRC through the production of carcinogens, cocarcinogens, or procarcinogen substances [ 29 ]. The direct interaction of gut microbes with the epithelial cells is limited due to the presence of mucosal barriers [ 31 ]. However, these microbes convert the complex chemicals provided by the host and dietary nutrients into a milieu metabolite which can be easily translocated across the mucosal barrier and play a role in tumorigenesis through multiple mechanisms, such as modifying signaling proteins [ 28 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are substantial reports that the general gut microbiota is associated with the initiation and progression of CRC through the production of carcinogens, cocarcinogens, or procarcinogen substances [ 29 ]. The direct interaction of gut microbes with the epithelial cells is limited due to the presence of mucosal barriers [ 31 ]. However, these microbes convert the complex chemicals provided by the host and dietary nutrients into a milieu metabolite which can be easily translocated across the mucosal barrier and play a role in tumorigenesis through multiple mechanisms, such as modifying signaling proteins [ 28 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The direct interaction of gut microbes with the epithelial cells is limited due to the presence of mucosal barriers [ 31 ]. However, these microbes convert the complex chemicals provided by the host and dietary nutrients into a milieu metabolite which can be easily translocated across the mucosal barrier and play a role in tumorigenesis through multiple mechanisms, such as modifying signaling proteins [ 28 , 31 ]. In previous studies, it has been demonstrated that the elevated gut microbes derived from secondary bile acids, such as deoxycholic acid, promote the development and progression of CRC [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are present at high levels in the GI tract, where they enable rapid turnover of intestinal epithelial cells and regulate specific eukaryotic gene expression among many other functions. For many decades now, polyamines have been implicated in tumorigenesis, including CRC ( Gerner and Meyskens, 2004 ; Peng et al, 2021 ), due to their essential role in cell proliferation. Bacterial TMA production has also been linked to the consumption of red meat (a source of carnitine) and cardiovascular disease ( Koeth et al, 2014 ).…”
Section: Microbiome-mediated Mechanisms and Impact On Homeostasismentioning
confidence: 99%
“…In healthy states, primary bile acids (BAs), including cholate and chenodeoxycholate, are synthesized from cholesterol in the liver and conjugated with glycine or taurine before excretion. The majority of primary BAs are reabsorbed in the ileum; however, a small proportion (approximately 5%) enter the colon where they are deconjugated and converted to secondary BAs, including deoxycholic acid and lithocholic acid, respectively, by the microbiota ( Peng et al, 2021 ). Dominant members of the healthy stool microbiome ( Human Microbiome Project Consortium, 2012 ), namely Firmicutes (including Clostridium spp., Ruminococcus gnavus and Faecalibacterium prausnitzii ) and Bacteroidetes, are potent BA deconjugators and secondary BA transformation is attributed to metabolic activity by the genera Bacteroides, Clostridium, Eubacterium, Lactobacillus , and Escherichia ( Duboc et al, 2013 ; Jia et al, 2018 ).…”
Section: Microbiome-mediated Mechanisms and Impact On Homeostasismentioning
confidence: 99%
“…Advancement of analytical techniques such as nuclear magnetic resonance (NMR) has enabled the quantitative identification of a wide range of metabolites using a very small volume of sample [ 14 ]. Metabolic profiling was already applied to the study of cancer biology [ 15 , 16 , 17 , 18 ], also with the aim of identifying potential predictive disease biomarkers. A recent study already identified potential biomarkers of AK through integrated metabolomics and histopathological analysis, with the aim of investigating the effects of the field cancerization treatment [ 19 ].…”
Section: Introductionmentioning
confidence: 99%